2014
DOI: 10.1007/s11605-014-2460-1
|View full text |Cite
|
Sign up to set email alerts
|

How to Treat an Appendiceal Inflammatory Mass: Operatively or Nonoperatively?

Abstract: We conclude that the high rate of recurrence and intervention in the nonoperative group and the high proportion of these patients who did not receive adequate follow-up despite the relatively high rate (5.9%) of bowel malignancy support the operative management of an appendiceal inflammatory mass. Noninterventional management or a percutaneous intervention should be reserved as a bridge to surgery for patients with a large accompanying abscess or as treatment for patients with significant comorbidity. If nonop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 14 publications
4
59
0
6
Order By: Relevance
“…It must be mentioned that this meta-analysis was subject to large heterogeneity [100]. Recent cohort studies draw opposite conclusions [101, 102]. They opt for a more aggressive surgical approach at time of presentation in case of an appendicular mass or appendicular abscess, based upon the idea that there is a relative high failure rate for non-surgical treatment [101, 102].…”
Section: Pre-operative Carementioning
confidence: 99%
“…It must be mentioned that this meta-analysis was subject to large heterogeneity [100]. Recent cohort studies draw opposite conclusions [101, 102]. They opt for a more aggressive surgical approach at time of presentation in case of an appendicular mass or appendicular abscess, based upon the idea that there is a relative high failure rate for non-surgical treatment [101, 102].…”
Section: Pre-operative Carementioning
confidence: 99%
“…It’s reported that 2 to 6% of acute appendicitis cases consist in inflammatory appendiceal mass [8], and recent series demonstrate an elevated incidence of malignant tumors in this organ, between 5.9 and 12% [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that appendiceal tumor detection rates in patients with a periappendicular mass up to 6.0-12.0%. 9,15 In our study, 45 (0.9%) of the appendectomy patients were found to have an appendiceal inflammatory mass (plastron appendicitis). Interval appendectomy was performed in these patients who were treated conservatively, 6-8 weeks later.…”
Section: Introductionmentioning
confidence: 52%